The Enhancing Postharvest Quality and Market Access: Adopting Integrated Ozone-Cold Storage Technology for Smallholder Farmers' Hygienic Produce - Ismail, Hasan (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Background: This community service program addresses the critical agricultural challenges of post-harvest loss in Asmorobangun Village, Kediri, specifically rapid product spoilage, inadequate storage, and unstable market prices. The focus is on introducing accessible technological solutions to farmers for hygienic post-harvest handling. Purpose of the Study: The purpose of this program is to implement and evaluate the effectiveness of ozone technology combined with cold storage in reducing post-harvest losses. The objectives are to extend the shelf life of horticultural products, improve their market quality, and empower farmers through participatory training and application. Methods: The implementation used a participatory approach, actively involving farmers in all stages: problem identification, socialization, design and assembly of a corona discharge–type ozone generator and cold storage units, equipment testing, technical training, and field assistance. Results: The combined use of ozone and cold storage significantly extended product shelf life—by 2–3 days at room temperature and up to 3–4 weeks with cold storage. The technology effectively maintained freshness, color, and texture while being user-friendly and eco-friendly. Farmers responded positively due to its economic benefits and improved product marketability. The program successfully established a replicable model for sustainable post-harvest management in similar farming communities.